Cardiologists and ONCologists Exercise PromoTion Study (CONCEPTS) - LeBreton, Kelli A., author; Leach, Heather J., advisor; Braun, Barry, committee member; Pergolotti, Mackenzi, committee member; Schuster, Steven R., committee member (Colorado State University. Libraries, 2018)
Background: Cardiovascular disease (CVD) and cancer are the two leading causes of death in the U.S. Survivors of CVD and cancer can benefit from exercise following a diagnosis to manage symptoms, improve quality of life, and reduce the risk of mortality. Physicians can play a key role in promoting exercise to their patients, yet the rates of discussion of exercise and referral to exercise programs are lower than expected among oncologists and cardiologists, given the evidence of benefit for their patients. Purpose: This aim of this study was to 1) compare cardiologist's and oncologist's the beliefs about exercise for their patients, 2) compare oncologist's and cardiologist's exercise promotion practices, 3) examine the relationship between physician's own exercise habits and their beliefs about exercise for their patients, and 4) examine the relationship between physician's beliefs about exercise for their patients, and their exercise promotion practices. Method: An online survey was distributed to practicing cardiologists, and medical and radiation oncologists in northern Colorado. The survey consisted of 22 questions in four categories; demographics, self-reported exercise behavior, exercise promotion practices, and beliefs about exercise for patients. activPAL accelerometers were used to objectively measure exercise levels. Results: Out of 154 surveys sent, 37.0% (N=57) were returned (N=25 cardiologists, N=32 oncologists), and N=12 cardiologists and N=6 oncologists wore the accelerometers. The survey found that 70% of oncologists and 79% of cardiologists agreed or strongly agreed that exercise reduces disease recurrence or increases the likelihood of survival to a similar extent, but more cardiologists disagreed, and more oncologists reported a neutral belief (FE(2)=9.681, p=.005, V=.429). A greater proportion of cardiologists (65%) reported discussing exercise at most or all visits compared to oncologists (35%) (χ2(2)=7.385, p=.029, V=.360). Oncologists were 8 times more likely to look for physical therapists when referring to exercise-based programs (χ2(1)=11.017, p=.001) whereas more cardiologists were 6 times more likely to look for certified exercise physiologists (χ2(1)=7.267, p=.009). Among both oncologists and cardiologists, step count and MVPA minutes were inversely related to the belief that exercise improves patients' well-being (rs=-.515, 95% CI [-.767, -.155] p=.034; rs=-.609, 95% CI [-.829, -.259], p=.009). Among cardiologists, there was an inverse relationship between MVPA minutes and the belief that exercise improves well-being in patients (rs=-.671, 95% CI [-.881, -.503], p=.024). Among oncologists, there was a positive association between break rate and believing their patients are capable of exercise (rs=.828, 95% CI [.664, .980], p=.042). However, there was no relationship between self-report exercise levels and beliefs about exercise for patients. Cardiologists who "agreed or strongly agreed" that exercise reduced recurrence or increased the likelihood of survival were 6.8 times more times likely to discuss exercise at most or all visits compared to those who were "neutral" or "disagreed" (FE(4)=9.351, p=.027, V=.514). Conclusions: Although cardiologists and oncologists generally shared positive beliefs about exercise for their patients, more oncologists were neutral in the belief that exercise can reduce recurrence or increase the likelihood of survival and more cardiologists disagreed. Further, the relationship between physicians' own exercise levels and their beliefs about exercise for the patients should be interpreted with caution due to small sample size with activPAL accelerometers. Cardiologists' beliefs about exercise reducing disease recurrence in patients influences their exercise promotion practices, but there were no other relationships. This may be due, in part, to systemic barriers, such as the need to address more pressing medical issues in a limited amount of time. Future studies need to identify why there is a gap between physicians holding positive beliefs about exercise for patients, yet not discussing or recommending exercise to the same extent in addition to interventions that target closing this gap.